Reliability and validity of the Vietnamese version of the Hamilton D-17 scale - Le-Nguyen-Thuy, Phuong; Nguyen-Dao-Uyen, Trang; Tran-Nguyen-Quynh, Anh; Thai, Truc Thanh; Ngo-Tich, Linh; Do-Van, Dung; Duong-Quy, Sy (Frontiers in Psychiatry, 2023)
Background While depression is a common mental disorder, the diagnosis of this condition is still challenging. Thus, there is a need to have a validated tool to help evaluate symptoms of depression. This study aimed to evaluate the reliability and validity of the Vietnamese version of the Hamilton D-17 scale. Methods A cross-sectional, descriptive, and validation study was conducted on 183 patients including 139 depressed and 44 non-depressed patients at the University Medical Center of Medicine and Pharmacy University at Ho Chi Minh City. Internal reliability and inter-rater reliability was measured using Cronbach's alpha and intraclass correlation coefficients (ICC). Confirmatory factor analysis (CFA) was used to evaluate construct validity. The Patient Health Questionnaire (PHQ9) was used to measure concurrent validity of the Hamilton D-17. Area under the ROC curve was used to measure criterion validity. Results Both Cronbach alpha coefficient and ICC were at good level at alpha = 0.83 and ICC = 0.83. CFA with a second-order model consisting of four factors fitted the data at good to excellent level. The SRMR (Standardized Root Mean Squared Residual) was 0.066, RMSEA (Root Mean Square Error of Approximation) (90% CI) was 0.053 (0.036–0.069), CFI (comparative fit index) was 0.93, TLI (Tucker Lewis index) was 0.92. The Hamilton D-17 and the PHQ-9 had a correlation coefficient of r = 0.77 (p < 0.001). The Hamilton D-17 had a very high level of criterion validity with AUC of 0.93 (0.88–0.98). Conclusion The Vietnamese version of the Hamilton D-17 scale has a high level of validity and reliability. The scale should be used to assess symptoms of depression among Vietnamese patients.